Akibat Hukum Pelaksanaan Kewajiban Penggugat Tidak Tepat Waktu Perspektif Fatwa DSN MUI Nomor 129/DSN-MUI/VII/2019: Studi Putusan Pengadilan Agama Kisaran Nomor:1333/Pdt.G/2023/PA. Kis - Iqbal Yudha Pratama; Tetty Marlina Tarigan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Implementation of obligations not on time or often referred to as default or breach of promise, where one party does not heed the terms of the agreement that has been agreed upon. According to the judge's decision in the aforementioned instance, a breach of promise, or default, occurs when the debtor fails to give what is required of him by the creditor, or fails to act as stipulated in the agreement, either intentionally or through negligence. By means of the Defendant's warning letters I, II, and III, which are evidenced here, the Plaintiff violated the terms of the contract since he disregarded them and failed to fulfill his responsibilities. Part three defines breach of contract or breach of promise as doing something that should not be done (al a'addi), not doing what should be done (al-taqshir), or going against what has been agreed upon (mukhalafat al-syuruth), based on DSN-MUI Fatwa Number 129 of 2019 in deciding the first point. According to point (d), which explains that the Plaintiff must pay the obligation after the agreed-upon period and in an amount less than agreed, the Plaintiff is considered to have breached his commitment in this situation and is in default. This research aims to examine how sharia economic disputes are handled, particularly when the Religious Court, which made the verdict, is in default. Normative juridical research, which makes reference to legal norms through decision studies, is the methodology employed. The study's conclusions are based on the judge's decision, which was made after taking into account the evidence showing that the plaintiff had in fact broken the terms of the agreement (defaulted). The judge's ruling in the primary case stated that the plaintiff's lawsuit was dismissed in its entirety and that the plaintiff would be responsible for paying the court's costs.